2008
DOI: 10.1002/ejsp.494
|View full text |Cite
|
Sign up to set email alerts
|

Motivations underlying attitudes: regulatory focus and majority versus minority support

Abstract: Drawing on regulatory focus theory, the present work examined the motivations underlying intergroup attitudes expressed under conditions of majority versus minority support. In two studies, participants expressed their attitudes towards equality and non-discrimination of foreigners and were informed that the equality and non-discrimination principle was supported by either a majority or a minority. Regulatory focus was assessed as the extent to which participants felt promotion-related and prevention-related e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
3
9
0
Order By: Relevance
“…Similar results were obtained for chronic avoidance motivation and failure on a task ( Idson et al, 2000 ) or outgroup members ( Shah et al, 2004 ) as NStim. Additional studies investigating chronic as well as situationally induced avoidance motivation observed similar results (e.g., Higgins and Tykocinski, 1992 ; Shah, 2003 ; Falomir-Pichastor et al, 2008 ; Yi and Baumgartner, 2008 ; Adams et al, 2011 ; Falomir-Pichastor et al, 2011 ). However, there are also a few studies that did not show this pattern or even a contradictory mapping of emotional tone and motivational orientation ( Faddegon et al, 2008 ; Yi and Baumgartner, 2009 ; Winterheld and Simpson, 2011 ; McKay-Nesbitt et al, 2013 ).…”
Section: Evidencesupporting
confidence: 59%
“…Similar results were obtained for chronic avoidance motivation and failure on a task ( Idson et al, 2000 ) or outgroup members ( Shah et al, 2004 ) as NStim. Additional studies investigating chronic as well as situationally induced avoidance motivation observed similar results (e.g., Higgins and Tykocinski, 1992 ; Shah, 2003 ; Falomir-Pichastor et al, 2008 ; Yi and Baumgartner, 2008 ; Adams et al, 2011 ; Falomir-Pichastor et al, 2011 ). However, there are also a few studies that did not show this pattern or even a contradictory mapping of emotional tone and motivational orientation ( Faddegon et al, 2008 ; Yi and Baumgartner, 2009 ; Winterheld and Simpson, 2011 ; McKay-Nesbitt et al, 2013 ).…”
Section: Evidencesupporting
confidence: 59%
“…This reasoning is supported by empirical evidence showing that attitudes changed via majority influence are less predictive of related behavioural intention than attitudes changed via minority influence (Martin, Martin, Smith, & Hewstone, 2007). Moreover, Falomir-Pichastor, Mugny, Quiamzade, and Gabarrot (2008) showed that agreement with majority views evokes feelings of quiescence and relaxation, whereas agreement with minority positions evokes feelings of cheerfulness (see Higgins, 1997; Shah & Higgins, 2001). These results suggest that individuals interpret their past behaviour as a function of the numerical support for it, and will engage to a lesser extent in consistent behaviour when they already fit normative prescriptions.…”
Section: Majority and Minority Supportmentioning
confidence: 99%
“…Conversely, people might feel more threatened when their past behaviour does not fit the normative prescriptions of a majority (vs. a minority) and, consequently, try harder to make up for their lack of effort. Accordingly, Falomir-Pichastor et al (2008) showed that disagreement with majority views elicits feelings of agitation (whereas disagreement with minority views elicits feelings of dejection and sadness). Consequently and according to classic normative influence literature, majorities may, at first, exert more influence than minorities.…”
Section: Majority and Minority Supportmentioning
confidence: 99%
“…Participants then read a one-page-long text describing the principle of “equality and non-discrimination” as a fundamental aspect of a functional modern society (e.g., “Equality between groups and most notably non-discrimination of minority groups proves a fundamental value for a society to function adequately”). We subsequently asked participants to imagine they had just done, first, something incongruent with these values (i.e., they discriminated against somebody), and second, something congruent with these values (i.e., they had not discriminated), and to report to what extent they would experience certain emotions as a result, in both cases (Falomir-Pichastor, Mugny, Quiamzade, & Gabarrot, 2008). The emotions proposed corresponded to either a promotion or a prevention focus (see Higgins et al, 1997; Shah & Higgins, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Non-surprisingly, participants reported more positive emotions when they imagined themselves not discriminating ( M = 5.61, SD = 1.26) than discriminating ( M = 2.74, SD = 1.27), F (1, 344) = 567.2, p < .001, η 2 p = .62. We hence reverse-coded the emotions reported when imagining discriminating to obtain an index of the strength of “congruent emotions” (see Falomir-Pichastor et al, 2008). We were then able to compute separate scores of promotion emotions and prevention emotions.…”
Section: Methodsmentioning
confidence: 99%